Regenerative and biomimetic strategies in spinal surgery - Sharma, A (2015)
Degenerative conditions of the spine are a major public health problem, leading to severe back pain, reduced quality of life and chronic disablement in a proportion of sufferers. For some of these patients, spinal fusion surgery is a treatment that can alleviate back pain and restore normal function. However, limitations in the availability of graft material mean that alternative grafts are needed and tissue-engineering approaches have been employed. Using a novel self-organising collagen scaffold combined with nano-hydroxyapatite and chondroitin sulphate and by employing the latest materials techniques, I have studied the osteogenic capability of a biomimetic graft for use in spinal fusion surgery. The mineralised collagen scaffold has compressive strength comparable to human cancellous bone and can support the proliferation of viable human mesenchymal stem cells. This porous scaffold can be combined with human mesenchymal stem cells to further promote bone growth, as evidenced by an upregulation in the levels of bone-forming genes and mineralisation of the scaffold. This scaffold can act as a carrier system for BMP-2, with wider application for other growth factors or drugs, providing sustained release when fabricated as a layer-by-layer scaffold. An alternative bone substitute for use in spinal surgery has been designed and characterised, with exciting potential for use in vivo.